Research progress on the immune mechanism of thyroid-related eye disease combined with dry eye - Yuhong Wang; Dan Chen; Lina Jin; Dongping Li (Journal of Ophthalmic Inflammation and Infection)
Abstract Thyroid associated eye disease combined with dry eyes is a common clinical disease and has gradually received clinical attention. Its onset is caused by various factors such as eyelid dynamic change and immune inflammation, involving tear secretion, tear discharge, tear quality and other aspects. This article systematically reviews the research related to its immune factors.